The effect of dietary alfalfa and flax sprouts on rabbit meat antioxidant content, lipid oxidation and fatty acid composition. (August 2015) - Dal Bosco, A.; Castellini, C.; Martino, M.; Mattioli, S.; Marconi, O.; Sileoni, V.; Ruggeri, S.; Tei, F.; Benincasa, P.
Abstract: The aim of this study was to determine the effect of dietary supplementation with flax and alfalfa sprouts on fatty acid, tocopherol and phytochemical contents of rabbit meat. Ninety weaned New Zealand White rabbits were assigned to three dietary groups: standard diet (S); standard diet + 20 g/d of alfalfa sprouts (A); and standard diet + 20 g/d of flax sprouts (F). In the F rabbits the Longissimus dorsi muscle showed a higher thio-barbituric acid-reactive value and at the same time significantly higher values of alpha-linolenic acid, total polyunsaturated and n-3 fatty acids. Additionally n-3/n-6 ratio and thrombogenic indices were improved. The meat of A rabbits showed intermediate values of the previously reported examined parameters. Dietary supplementation with sprouts produced meat with a higher total phytoestrogen content. The addition of fresh alfalfa and flax sprouts to commercial feed modified the fat content, fatty acid and phytochemical profile of the meat, but the flax ones worsened the oxidative status of meat. Highlights: Supplementation of rabbit diets with fresh flax or alfalfa sprouts. Both species modified fat content, fatty acid & phytochemicals of rabbit meat. Flax decreased n-6/n-3 ratio and thrombogenic index but worsened meat oxidative status. Both type of sprouts improved meat phytoestrogen content. First evidence of bioactive compound transfer from sprouts to rabbit meat.